2017
DOI: 10.1590/1678-4162-9241
|View full text |Cite
|
Sign up to set email alerts
|

Gamma radiation treatment applied to microbial decontamination of products derived from eggs collected from the retail market in São Paulo

Abstract: The quality of products derived from eggs depends on the quality of the raw material source and the industrial production. The contamination by fungi and bacteria can occur after exposure of the product in the retail market. The objective of this study was to evaluate the microbiological quality of 60 samples of derivated egg products and evaluate the effects of gamma radiation of cobalt-60, using the dose of 5 and 10 kGy, for decontamination of products collected in the retail market in the São Paulo city. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…This is to be expected, since irradiation is one of the few processes that eliminates disease-causing microorganisms from foods and guarantees high hygienic quality (Adu-Gyamfi et al, 2012). The results corroborate the findings of Aquino, Lui, and Correa (2017), who observed that for the complete elimination of microorganisms in egg powder, it was necessary to use doses around 10 kGy. Egg disinfection has two purposes.…”
Section: Effect Of Gamma Irradiation On Microbiological Qualities Of supporting
confidence: 85%
“…This is to be expected, since irradiation is one of the few processes that eliminates disease-causing microorganisms from foods and guarantees high hygienic quality (Adu-Gyamfi et al, 2012). The results corroborate the findings of Aquino, Lui, and Correa (2017), who observed that for the complete elimination of microorganisms in egg powder, it was necessary to use doses around 10 kGy. Egg disinfection has two purposes.…”
Section: Effect Of Gamma Irradiation On Microbiological Qualities Of supporting
confidence: 85%
“…Chloramphenicol (0.05 g L -1 ) was added to inhibit bacteria, since chloramphenicol is a broad-spectrum antibiotic inhibitory to a wide range of gramnegative and gram-positive bacteria without affecting fungal growth (Haley, Trandel, & Coyle, 1980). The plates were incubated at 25ºC for 7 days in a standard Biochemical Oxygen Demand (BOD) incubator for growth of fungi cultures (Aquino, Lui, & Corrêa, 2017). After incubation, the Petri dishes were visually observed for fungal counts in colony forming units per gram of sample (cfu g -1 ).…”
Section: Methodsmentioning
confidence: 99%